1998
DOI: 10.1094/pdis.1998.82.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cotton Seedling Damping-off in the Field by Burkholderia (Pseudomonas) cepacia

Abstract: Four field trials were conducted in April 1995 and 1996 in Arizona to compare the effectiveness of: 1, a soil drench of isolate D1 of Burkholderia (Pseudomonas) cepacia; 2, isolate D1 barley meal formulation; 3, Deny seed treatment (a peat moss-based formulation of B. cepacia); 4, Deny soil drench; 5, Kodiak seed treatment (a formulation of Bacillus subtilis); 6, a mixture of three fungicides (metalaxyl, triadimenol, and thiram) seed treatment; and 7, a mixture of metalaxyl, triadimenol, thiram, and Kodiak see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 15 publications
1
21
0
1
Order By: Relevance
“…In field trials, a soil drench of Burkholderia cepacia improved plant stand in R. solani infested soils, possibly due to the production of growthinhibiting antifungal compounds (Zaki et al, 1998). Trichoderma spp.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In field trials, a soil drench of Burkholderia cepacia improved plant stand in R. solani infested soils, possibly due to the production of growthinhibiting antifungal compounds (Zaki et al, 1998). Trichoderma spp.…”
Section: Referencesmentioning
confidence: 99%
“…The importance of increasing the fitness of the biocontrol agent in the field was highlighted in field tests in Arizona, where the effectiveness of Burkholderia cepacia, locally isolated from cotton fields was compared with that of several commercial products, including Kodiak ® and Deny ® . The local strain showed the most effective control of damping-off caused by R. solani, especially when combined with chemical fungicides (Zaki et al, 1998).…”
Section: Considerations For Use and Commercialisation Of Pgp Microbesmentioning
confidence: 99%
“…While ARR at the molecular level has been studied with respect to leaf pathogens, little discussion has focused on root defense strategies and their role in ARR. However, there are some indirect correlations; for example, cotton (Zaki et al, 1998) or bean (Nicoli et al, 2012) plants are more susceptible to root disease (Rizoctonia solani or Fusarium root rot, respectively) at the seedling stage. Recent studies have shown that root secretion of defense-related proteins is enhanced during flowering time (De-la-Pena et al, 2010), suggesting an involvement of plant roots in ARR.…”
Section: Introductionmentioning
confidence: 99%
“…P. fluorescens strain BL915 was effective against R. solani by producing pyrrolnitrin (Hill et al 1994). In a study, Zaki & Kersten (1998) …”
Section: In Vivo Experimentsmentioning
confidence: 99%